Microwave Synthesis, Spectral, Thermal and Antimicrobial Studies of Some Co(II), Ni(II) and Cu(II) Complexes Containing 2-Aminothiazole Moiety - A. P. Mishra; H. Purwar; Rajendra K. Jain; S. K. Gupta (E-Journal of Chemistry)
Some new Schiff base metal complexes of Co(II), Ni(II) and Cu(II) derived from 4-chlorobenzylidene-2-aminothiazole (CAT) and 2-nitrobenzylidene-2-aminothiazole (NAT) have been synthesized by conventional as well as microwave methods. These compounds have been characterized by elemental analysis, FT-IR, FAB-mass, molar conductance, electronic spectra, ESR, magnetic susceptibility, thermal, electrical conductivity and XRD analysis. The complexes are coloured and stable in air. Analytical data revealed that all the complexes exhibited 1:2 (metal:ligand) ratio with coordination number 4 or 6. FAB-mass and thermal data show degradation pattern of the complexes. The thermal behavior of metal complexes shows that the hydrated complexes loses water molecules of hydration in the first step; followed by decomposition of ligand molecules in the subsequent steps. The crystal system, lattice parameter, unit cell volume and number of molecules in unit cell in the lattice of complexes have been determined by XRD analysis. XRD patterns indicate crystalline nature for the complexes. The solid state electrical conductivity of the metal complexes has also been measured. Solid state electrical conductivity studies reflect semiconducting nature of the complexes. The Schiff base and metal complexes show a good activity against the Gram-positive bacteria; Staphylococcus aureus and Gram-negative bacteria; Escherichia coli and fungi Aspergillus niger and Candida albicans.